Storytelling Podcast as an Alternative Learning Tool for Early Childhood Education: A TPACK-Based Reflection - Formen, Ali; Waluyo, Edi (Al-Athfal: Jurnal Pendidikan Anak, 2023)
Purpose – This article reports on a project to facilitate teachers’ digital skill improvement. The context of the project itself was the past COVID-19 pandemic, which paralized the education sector, including the closure of early childhood education (ECE) centers. While remote, online learning was highly recommended to face disastrous situation such as pandemic, in practice, especially at the ECE level, online learning faces complex challenges. On the other hand, teachers were not adequately prepared for online and digital learning. Design/methods/approach – This study combined developmental and conventional descriptive methods. The participants (15 people) were teachers, with various backgrounds of work experience (2 to over 7 years), with good internet access skills. Data and information were collected through observation, interviews, and documentation; followed by descriptive analysis. Findings – These teachers found that Podcasts could be an alternative and a variation of digital learning media. Making and using podcasts can also be an entry point in strengthening the integration of Technological and Pedagogical Content Knowledge (TPACK) in the ECE context. Research implications/limitations – While storytelling Podcast as ECE learning tool was used limitedly during the COVID-19 period, its uses may last beyond the pandemic time provided systematic integration of digital technology and skills associated with it into ECE sector is met.  Practical implications – This study implies that storytelling podcasts can be an alternative learning tool in the situation where teacher-student face-to-face interaction is less possible. Originality/value – The emergency period prevented teacher-student direct contacts. This study contributes to providing an alternative to learning in an emergency situation. Paper type Research paper